The Contribution of Slompn UPI to Young Athlete Development: A Descriptive Analysis of 2022–2023 Achievement - Deni Maulana (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to analyze the contribution of the National Potential Youth Sports Training Center (SLOMPN) of the Indonesia University of Education in coaching young athletes with outstanding achievements during the 2022-2023 period. Using a quantitative descriptive method with secondary data analysis techniques, this study examined 72 competition participations of 17 athletes out of a total population of 19 athletes distributed across three sports: Taekwondo, Athletics, and Archery. Results demonstrate a remarkably high success rate of 94.4% in medal acquisition, with 59.7% being gold medals. Taekwondo dominates with 88.9% of total achievements and a gold medal rate of 65.6%, while Athletics and Archery remain in developmental phases. Performance distribution shows 51.4% achieved at provincial level, 38.9% at national level, and 2.8% at international level. Individual performance analysis identifies adequate talent pool depth with 10 athletes achieving 4 or more medals. Findings reveal that SLOMPN UPI’s success is supported by effective selection systems, ideal coach-athlete ratio (6.5:1), structured training programs, and strategic university collaboration. However, limited international exposure (2.8%) and high dependency on one sport require attention. This research reinforces the proposition that sport-specialized schools integrated with universities can serve as an effective blueprint for youth athlete development in Indonesia, noting the need for increased international exposure and sport diversification for long-term sustainability.